Scooby-Doo! World of Mystery 45 Namibia - Skeleton Coast - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
The gang find themselves on the spooky Skeleton Coast where the skeletons seem to have come alive...
Keywords: Juvenile literature-Fiction